Gender Equality, Disability and Social Inclusion Approach to Disaster Management Policy: The Case of the Bali Disaster Response Authority - Rimbawan, I Putu Dedy; Nurhaeni, Anik (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2023)
This article describes the application of the GEDSI (Gender Equality, Disability, and Social Inclusion) approach to disaster management policies with special reference to the Province of Bali. The province, which frequently experiences natural disasters such as earthquakes, volcanic eruptions and floods, recognizes the need to pay attention to gender differences, disabilities and social inclusion in all aspects of disaster management. The GEDSI approach promotes active participation and an equal role for all community members in dealing with disasters. The findings show that Bali is committed to ensuring equal access to information, protection and disaster management services for vulnerable groups. It seeks to integrate a gender perspective in disaster management planning, including ensuring women's participation in decision-making and their involvement in policy implementation. In addition, the GEDSI approach also emphasizes social inclusion and the needs of people with disabilities. Bali seeks to remove physical and social barriers that may impede the participation and accessibility of persons with disabilities during disasters. Disabled persons-friendly facilities and services are provided, and disability groups are involved in policy planning and evaluation. With the GEDSI approach, disaster management in Bali can be inclusive and responsive to the needs of all individuals. This approach will ensure equity, respect human rights and enhance sustainability in the face of natural disasters.